Cognitive deficits in schizophrenia and other neuropsychiatric disorders: Convergence of preclinical and clinical evidence - Ales Stuchlik (Frontiers Research Topics, 2015)
Neuropsychiatric diseases, such as schizophrenia, Alzheimer's disease, and etc., represent a serious medical and socioeconomic problems. These diseases are often accompanied by impairments of cognitive function, e.g., abstract thinking, decision-making, attention, and several types of memory. Such deficits significantly disrupt quality of life and daily functioning of patients. Cognitive deficits in neuropsychiatric diseases are associated with alterations of brain morphology and function, and are often resistant to therapeutic interventions. In schizophrenia and related disorders, cognitive deficits are also defined as endophenotypes, i.e. measurable phenotypes linking these disaeses with discrete heritable and reproducible traits. This points to the importance of elucidating these endophenotypes in translational studies. Animal models may not mimic the full spectrum of clinical symptoms, but may act as analogies of particular behaviors or other pathological outcomes. They are useful to search for the etiology of particular psychiatric illnesses and novel therapeutics. Moreover, several behavioral tests to measure cognitive performance in rodents and other species have been implemented. The primary focus of the present topic is to provide up-to-date information on cognitive deficits of neuropsychiatric disorders, such as schizophrenia. This Research Topic also delineates future directions for translational studies aimed at developing novel treatments/interventions of cognitive disturbances.